Ethnicity and the association between anthropometric indices of obesity and cardiovascular risk in women: a cross-sectional study - Goh, Louise; Dhaliwal, Satvinder; Welborn, T.; Lee, Andy; Della, Phillip (B M J Group, 2014)
Objectives: The objectives of this study were to determine whether the cross-sectional associations between anthropometric obesity measures, body mass index (BMI), waist circumference (WC) and waist-to hip ratio (WHR), and calculated 10-year cardiovascular disease (CVD) risk using the Framingham and general CVD risk score models, are the same for women of Australian, UK and Ireland, North European, South European and Asian descent. This study would investigate which anthropometric obesity measure is most predictive at identifying women at increased CVD risk in each ethnic group. Design: Cross-sectional data from the National Heart Foundation Risk Factor Prevalence Study. Setting: Population-based survey in Australia. Participants: 4354 women aged 20–69 years with no history of heart disease, diabetes or stroke. Most participants were of Australian, UK and Ireland, North European, South European or Asian descent (97%).Outcome measures: Anthropometric obesity measures that demonstrated stronger predictive ability of identifying women at increased CVD risk and likelihood of being above the promulgated treatment thresholds of various risk score models. Results: Central obesity measures, WC and WHR, were better predictors of cardiovascular risk. WHR reported a stronger predictive ability than WC and BMI in Caucasian women. In Northern European women, BMI was a better indicator of risk using the general CVD (10% threshold) and Framingham (20% threshold) risk score models. WC was the most predictive of cardiovascular risk among Asian women. Conclusions: Ethnicity should be incorporated into CVD assessment. The same anthropometric obesity measure cannot be used across all ethnic groups. Ethnic-specific CVD prevention and treatment strategies need to be further developed.